Fisioterapia en Parálisis Braquial Obstétrica - Telenchana Medranda, Cynthia Estefania (2022)
ABSTRACT: The research project was carried out with the bibliographic review modality since a search was done for high-impact scientific articles on the subject of "Physiotherapy in obstetric brachial paralysis" the aim was to analyze the current information detailing different physiotherapeutic techniques used in patients with obstetric brachial paralysis, the importance of physical rehabilitation in this pathology is evident. In the search, 86 scientific articles were collected, 30 were selected for the investigation, those had a more excellent score than or equal to 6 according to the PEDro scale. Studies from 2011 to the present were also included. The ScienceDirect, PubMed, Scielo, ProQuest, Scopus, Elsevier, Pedro, and Google Scholar databases were used to collect articles in Spanish, English, Portuguese, and French. The results reveal that physiotherapy is effective for rehabilitation in patients with obstetric brachial paralysis, and several techniques contribute to the functional recovery of the upper extremity. In addition, according to the authors, it can be affirmed that with early intervention, better results can be obtained